Social Innovation: Emancipation or More of the Same? (Inovação Social: Emancipação ou Mais do Mesmo?) (Emancipação, 2020)
The article discusses the existing convergences between Social Innovation and Emancipation. A systematic literature review was carried out in order to understand the motivations that lead to Social Innovation. Inaddition, some concrete cases of innovations in the literature reviewed have been described.
Keywords: Social Innovation, Emancipation; Top-Down Innovations; Bottomup innovations; Hybrid Innovations.